2017
DOI: 10.1186/s12974-017-0832-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142 regulates inflammation and T cell differentiation in an animal model of multiple sclerosis

Abstract: BackgroundMicroRNAs have emerged as an important class of modulators of gene expression. These molecules influence protein synthesis through translational repression or degradation of mRNA transcripts. Herein, we investigated the potential role of miR-142a isoforms, miR-142a-3p and miR-142a-5p, in the context of autoimmune neuroinflammation.MethodsThe expression levels of two mature isoforms of miR-142 were measured in the brains of patients with multiple sclerosis (MS) and the CNS tissues from mice with exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 62 publications
2
82
0
Order By: Relevance
“…TGFBR1 has been shown in several studies to be implicated in AD pathogenesis (Caraci et al, 2012;Chen, Ke, Lu, Qiu, & Peng, 2015;Flanders, Lippa, Smith, Pollen, & Sporn, 1995;Lippa, Flanders, Kim, & Croul, 1998;Tesseur et al, 2006;Wyss-Coray et al, 2002). The regulation of TGFBR1 expression by miR-142-3p has been experimentally confirmed at mRNA and protein levels in previous studies (Talebi et al, 2017;Yang et al, 2017). Our differential expression analysis for all miR-142-3p target genes demonstrated that TGFBR1 was significantly downregulated in miR-142-3p overexpressing human iPS-derived NPCs and the top target gene upregulated in the hippocampus of miR-142 KO mice.…”
supporting
confidence: 66%
“…TGFBR1 has been shown in several studies to be implicated in AD pathogenesis (Caraci et al, 2012;Chen, Ke, Lu, Qiu, & Peng, 2015;Flanders, Lippa, Smith, Pollen, & Sporn, 1995;Lippa, Flanders, Kim, & Croul, 1998;Tesseur et al, 2006;Wyss-Coray et al, 2002). The regulation of TGFBR1 expression by miR-142-3p has been experimentally confirmed at mRNA and protein levels in previous studies (Talebi et al, 2017;Yang et al, 2017). Our differential expression analysis for all miR-142-3p target genes demonstrated that TGFBR1 was significantly downregulated in miR-142-3p overexpressing human iPS-derived NPCs and the top target gene upregulated in the hippocampus of miR-142 KO mice.…”
supporting
confidence: 66%
“…Many miRNAs have functioned as important regulators of the immune system [33,34,[43][44][45][46]. In particular, miR-155 is known to be a crucial regulator orchestrating the role of numerous acquired and native immune cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-33 reduces SREBP-1c protein expression and deletion of miR-33 results in marked worsening of HFD-induced obesity and liver steatosis in mice [54]. Only a few reports indicated that miR-142a-5p is involved in vascular development and integrity [55], neutrophil development [56], and inflammation and T-cell differentiation [57]. Currently, the physiological roles of miR-142a-5p have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the physiological roles of miR-142a-5p have not been well studied. Only a few reports indicated that miR-142a-5p is involved in vascular development and integrity [55], neutrophil development [56], and inflammation and T-cell differentiation [57]. Our results extended the recognition of miR-142a-5p functions and given the importance of SREBP-1c in the control of lipid homeostasis, suppression of SREBP-1c by miR-142a-5p would establish a connection among diverse pathophysiological conditions such as hyperlipidemia, cardiovascular remodeling, and innate immunity.…”
Section: Discussionmentioning
confidence: 99%